Strategi Pengembangan Bisnis Budidaya Ikan Lele Di Usaha Perikanan Rakyat - Dwi Yani Elfrida (Jurnal Niaga & Bisnis (e-journal), 2015)
The purpose of this study was to identify factors internal and external factors that are owned Usaha Perikanan Rakyat and determine appropriate development strategy to be implemented in the fishery business people in the future. The method used in this study is the descriptive research method. Informants were used in the research is the key informants that business owners. The analytical tool used in this study is the SWOT analysis matrix IFAS (Internal Factors Analysis Summary), matrix EFAS (External Factors Analysis Summary), and SWOT Analysis Diagram. Based on the analysis that has been conducted on the environmental factors that the company's internal environment and the external environment. In Internal Matrix Analysis Summary (IFAS), the power factor worth getting subtotals weakness factor of 2.1 and 0.6. While the External Matrix Analysis Summary (EFAS) factors showedodds of getting subtotal sworth 1.8 and 0.7 worth of threat factors. So it can be concluded that the position of the Usaha Perikanan Rakyat in  SWOT Analysis Diagram located on the first quadrant with an aggressive strategy or growth strategies. Aggressive strategies that can be implementedis to increase sales and maintain production volumes and expand market share. The design of these strategies can be appliedin Usaha Perikanan Rakyat in the futurein order tomaximizethe poweravailableby utilizingexisting opportunities.Keywords: strategy, aquaculture, catfish, external factors, internal factors, SWOT analysis